Hubungan Dukungan Sosial Keluarga dengan Perilaku Perawatan Diri pada Klien Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Kaliwates, Jember - Wahyuningtias Rahmadani; Hanny Rasni; Kholid Rosyidi Muhammad Nur (Pustaka Kesehatan, 2019)
Type 2 diabetes mellitus (T2DM) is a metabolic disease that can cause various chronic complications and they can be minimized by self-care. One of the factors that affect self-care in diabetic clients is family social support. The aim of the research was to analyze the correlation between family social support and self care behavior client with T2DM)in the area of Kaliwates public health center, Jember. This research applied an observational analytic design with cross-sectional approach. A total of 84 respondents were enrolled in this study by using purposive sampling technique. The data collection method used the HDFSS (Hensarling Diabetes Family Support Scale) and SDSCA (Summary of Diabetes Self Care Activity) questionnaires, it conducted on January 7th-22nd 2019. The data analysis used Spearman correlation test with a significance level of 0.05.The result showed that median of the family social support was 86 with a minimum value of 69 and a maximum value of 106, whereas the mean value of self-care behaviour was 2,27 days with a standard deviation of 0.45 days. There was a significant positive correlation between family sosial support and self-care behaviour (p value: 0.001; r; +0.378), meaning that the higher the level of family social support the better the self-care behaviour. This study suggests the importance of assessing family social support to improve self-care in clients with type 2 diabetes mellitus.